1995
DOI: 10.1093/geront/35.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Residents at Risk of Hospitalization and the Characteristics of Their Hospital Stays

Abstract: Little national data have been available to guide the design of programs aimed at reducing the hospitalization of nursing home residents. This article uses the 1987 National Medical Expenditure Survey to identify elderly nursing home residents with an elevated risk of hospitalization and the reasons for and outcomes of residents' hospital stays. Study findings include an elevated risk of hospitalization for residents with one of several different primary diagnoses and a rise in risk as ADL dependence increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 0 publications
5
76
0
Order By: Relevance
“…One possibility is that patients admitted with dementia have fewer comorbid conditions requiring expensive medical interventions compared to individuals with no dementia. This interpretation is consistent with research conducted by Murtaugh and Freiman (1995) and Fried and Mor (1997); both studies found that nursing home residents with dementia were significantly less likely to be hospitalized compared to those with no dementia. Another possible reason for lower utilization rates among nursing home residents with dementia is they are treated less aggressively for other medical conditions, possibly as a result of advance directives.…”
supporting
confidence: 90%
“…One possibility is that patients admitted with dementia have fewer comorbid conditions requiring expensive medical interventions compared to individuals with no dementia. This interpretation is consistent with research conducted by Murtaugh and Freiman (1995) and Fried and Mor (1997); both studies found that nursing home residents with dementia were significantly less likely to be hospitalized compared to those with no dementia. Another possible reason for lower utilization rates among nursing home residents with dementia is they are treated less aggressively for other medical conditions, possibly as a result of advance directives.…”
supporting
confidence: 90%
“…N ursing home residents frequently develop lower respiratory tract infections, mostly pneumonia and bronchitis, [1][2][3][4][5] with estimated 30-day mortality from pneumonia or lower respiratory tract infection varying between 10% and 30%. 3,[6][7][8][9] Because meaningful cultures from specimens are rarely obtained in practice, 10,11 antibiotic treatment is usually empiric.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to support the treatment of certain conditions-such as incontinence [108], pressure sores [109], infections [10,14,18,29,[110][111][112][113], diabetes mellitus [6,114], minor trauma [12, 25,54] and falls [14,17,54,[115][116][117][118][119][120]-in nursing homes. We need research to compare nursinghome care with hospital treatment to ensure that any changes improve the management of these patients and does not exclude them from the best possible care.…”
Section: Resultsmentioning
confidence: 99%
“…The prognosis for some older people after hospitalization, particularly emergency admission, is poor [12,14,16,17,20,22,24,25,27,30,32,41,57,73,74], given the attendant risk of further complications [12,18,30,38,40,42,44]. Hence, the need to review how best to manage acutely ill nursing-home residents [75] (especially those over 85).…”
Section: Introductionmentioning
confidence: 99%